The Potential In Vitro Inhibitory Effects of Neurokinin-1 Receptor (NK-1R) Antagonist, Aprepitant, in Osteosarcoma Cell Migration and Metastasis. (20th September 2022) - Alsaeed, Mohammed Ali; Ebrahimi, Safieh; Alalikhan, Abbas; Hashemi, Seyedeh Fatemeh; Hashemy, Seyed Isaac
Abstract : Background. Osteosarcoma, the most frequent osteogenic malignancy, has become a serious public health challenge due to its high morbidity rates and metastatic potential. Recently, the neurokinin-1 receptor (NK-1R) is proved to be a promising target in cancer therapy. This study is aimed at determining the effect of aprepitant, a safe and Food and Drug Administration (FDA) approved NK-1R antagonist, on osteosarcoma cell migration and metastasis, and to explore its underlying mechanism of action. Methods. Colorimetric MTT assay was employed to assess cell viability and cytotoxicity. A wound-healing assay was used to examine migration ability. The desired genes' protein and mRNA expression levels were measured by western blot assay and quantitative real-time PCR (qRT-PCR), respectively. Gelatinase activity was also measured by zymography. Results. We found that aprepitant inhibited MG-63 osteosarcoma cell viability in a dose-dependent manner. We also observed that aprepitant inhibited the migrative phenotype of osteosarcoma cells and reduced the expression levels and activities of matrix metalloproteinases (MMP-2 and MMP-9). Aprepitant also reduced the expression of an angiogenic factor, VEGF protein, and NF- κ B as an important transcriptional regulator of metastasis-related genes. Conclusion. Collectively, our observations indicate that aprepitant modulates the metastatic behavior of human osteosarcoma cells, which may be applied to an effective therapeutic approach for patients with metastatic osteosarcoma.